Metabolomics: uncovering insights into obesity and diabetes - Fazliana, Mansor; Gee, Tikfu; Lim, Shu Yu; Tsen, Poh Yue; Nor Hanipah, Zubaidah; Zainal Abidin, Nur Azlin; Zhuan, Tan You; Mohkiar, Farah Huda; Ahmad Zamri, Liyana; Ahmad, Haron; Draman, Mohd Shazli; Yusaini, Noorizatul Syahira; et al. (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Obesity is a complex, diverse, and multifactorial disease that has become a significant public health concern. It is a modifiable risk factor for developing type 2 diabetes (T2D). The current classification systems rely on anthropometric measurements, such as body mass index (BMI), which cannot capture the physiopathological diversity of this disease. This study aimed to analyze the metabolic signatures of obesity and diabetes using 1H-nuclear magnetic resonance (NMR). Obese patients with BMI ≥ 25 kg/m2 (according to the Asian cut-off value) with different diabetes status scheduled to undergo metabolic-bariatric surgery at three hospitals were prospectively recruited for this study. Plasma samples of 111 obese patients and 26 healthy controls were analyzed by 1H-NMR. When compared among groups with different diabetes statuses, four clusters with no differences in BMI but different metabolomics profiles were obtained. These clusters highlight intricate metabolic relationships associated with obesity and diabetes. This study demonstrated the benefits of using precision techniques like 1H-NMR to better early detection, substantially decreasing the risk of developing T2D and its related complications. This study is the first to report on metabolic markers and altered metabolic profiles of T2D and prediabetes among obese Malaysians with a BMI cut-off value for the Asian population.